In vitro dentin permeability after application of Gluma® desensitizer as aqueous solution or aqueous fumed silica dispersion - Hiroshi Ishihata; Werner J Finger; Masafumi Kanehira; Hidetoshi Shimauchi; Masashi Komatsu (University of São Paulo, 2011)
OBJECTIVES: To assess and to compare the effects of Gluma® Desensitizer (GDL) with an experimental glutaraldehyde and HEMA containing fumed silica dispersion (GDG) on dentin permeability using a chemiluminous tracer penetration test. MATERIAL AND METHODS: Twenty disc-shaped dentin specimens were dissected from extracted human third molars. The dentin specimens were mounted in a split chamber device for determination of permeability under liquid pressure using a photochemical method. Ten specimens were randomly selected and allocated to the evaluation groups Gluma® Desensitizer as aqueous solution and glutaraldehyde/HEMA as fumed silica dispersion, respectively. Dentin disc permeability was determined at two pressure levels after removal of smear with EDTA, after albumin soaking, and after application of the desensitizing agents. Two desensitizer-treated and rinsed specimens of each group were examined by scanning electron microscopy (SEM) for surface remnants. RESULTS: Comparatively large standard deviations of the mean EDTA reference and albumin soaked samples permeability values refected the differences of the dentin substrates. The mean chemiluminescence values of specimen treated with GDL and GDG, respectively, were signifcantly reduced after topical application of the desensitizing agents on albumin-soaked dentin. The effects of GDL and GDG on permeability were not signifcantly different. Treated specimens showed no surface remnants after rinsing. CONCLUSIONS: The experimental desensitizer gel formulation reduced dentin permeability as effectively as the original Gluma® Desensitizer solution.